Role of Punkampal Kiranthy oil in the Management of Senkiranthy in Infants - Nithyapriya, S.; Sivashanmugarajah, S. (Global Academic Research Institute Colombo, Sri Lanka, 2021)
Senkiranthy is one of the commonest skin problems in infants. Siddha pediatrics texts classified Kiranthy into two types they are Senkiranthy and Karumkiranthy, Karumkiranthy is a rare phenomenon. Pararasasegaram and Balaroga Nidhana has mentioned etiological factors, sign and symptoms and treatment of Kiranthy diseases. Formation of slightly elevated red patches over the body, mild itching, restlessness, abdominal discomfort are the common symptoms of the Senkiranthy. The objective of this study was to assess the effectiveness of the Punkampaal Kiranthy oil in management of Senkiranthy infants. This study was carried out from March 2015 to June 2015 at the Cellaiyah memorial Siddha Ayurvedic Medical centre, Vavuniya, Punkampal Kiranthy oil used as an external medicine. It was prepared at the above Medical centre. 30 infants were treated for Senkiranthy during this period. This disease has been studied based on the Siddha Medical literatures, clinical findings with patients and prognosis. The results were assessed on the basis of subjective and objective improvements. 83% (25) of senkiranthy infants got good results within two weeks.10 % (3) cured from kiranthy with in 1 month. Only 7 % (2) had not got any improvements. No adverse effective were noted during the treatment periods. This study revealed that external application of Punkampaal Kiranthy oil was effective for Senkirunthy in infants,
Keywords: Senkiranthy; Punkampal kiranthy oil; Infants; Karumkiranthy